Regulating two-sided markets: An empirical investigation - Santiago Carbó Valverde; Sujit Chakravorti; Francisco Rodriguez Fernandez (Federal Reserve Bank of Chicago, 2010)
Two-sided market theory predicts that platforms may subsidize the participation of one type of agent by extracting surplus from another type to internalize indirect network externalities. However, few empirical studies exist to evaluate the impact of government intervention in these markets. We use confidential bank-level data to study the impact of government-encouraged fee reductions for payment card services when merchant acceptance is not complete. We find that consumer and merchant welfare improved when the interchange fees, transfers among banks, were reduced. Furthermore, bank revenues increased because the increase in the number of transactions offset the decrease in the per-transaction revenue.
Keywords: L11; G21; D53; 330; payment choice; merchant adoption; network competition